Effect of Escin Alone or in Combination with Antifungal Agents on Resistant Candida glabrata Biofilms: Mechanisms of Action - Angela Maione; Marianna Imparato; Marilena Galdiero; Elisabetta de Alteriis; Antonia Feola; Emilia Galdiero; Marco Guida (MDPI AG, 2023)
Nowadays, the increase in antimicrobial-resistant fungi (AMR) is certainly a major health concern, and the development of alternative therapeutic strategies has become crucial. Natural products have been used to treat various infections, and their chemical properties contribute to the performance of their biological activities, such as antifungal action. The various virulence factors and mechanisms of resistance to antifungals contribute to making Candida glabrata one of the most frequent agents of candidiasis. Here we investigate the in vitro and in vivo activity of β-escin against Candida glabrata. The β-escin MICs were determined for a reference strain and two clinical isolates of C. glabrata. Furthermore, growth kinetics assays and biofilm inhibition/eradication assays (crystal violet) were performed. The differences in the expression of some anti-biofilm-associated genes were analyzed during biofilm inhibition treatment so that reactive oxygen species could be detected. The efficacy of β-escin was evaluated in combination with fluconazole, ketoconazole, and itraconazole. In addition, a Galleria mellonella infection model was used for in vivo treatment assays. Results have shown that β-escin had no toxicity in vitro or in vivo and was able to inhibit or destroy biofilm formation by downregulating some important genes, inducing ROS activity and affecting the membrane integrity of C. glabrata cells. Furthermore, our study suggests that the combination with azoles can have synergistic effects against C. glabrata biofilm. In summary, the discovery of new antifungal drugs against these resistant fungi is crucial and could potentially lead to the development of future treatment strategies.